Prevalence of therapeutic competitions in pharmacotherapy of users of Family Health Units in Ribeirão Preto, São Paulo (Research, Society and Development, 2021)
In the current epidemiological scenario, there is a high frequency of chronic non-communicable diseases with the increase in the use of drugs and therapeutic competitions. Thus, the aim of this study was to estimate the prevalence and identify therapeutic competitions in users who were followed up in six Family Health Units in Ribeirão Preto, São Paulo. This is a retrospective, longitudinal, descriptive and exploratory study with a sample consisting of 226 participants. Most were elderly (69.5%), belonged to the female sex (63.7%), were sedentary (48.2%) and had four or five chronic non-communicable diseases (50.8%), the most frequent being systemic arterial hypertension. The potential risk for the occurrence of therapeutic competitions was estimated at 64.2%. Among them, therapeutic competition between beta-blockers, used for the treatment of arterial hypertension, and type 2 diabetes mellitus stood out. The data show the need for a comprehensive approach in the care of the individual with multimorbidities in Primary Health Care. In addition, it alerts the risks of therapeutic competitions and the importance of monitoring the complications of the index disease in the presence of potential therapeutic competition.